Engaging zwitterions in carbon-carbon and carbon-nitrogen bond- forming reactions: a promising synthetic strategy - Nair, Vijay; Menon, Rajeev S.; Sreekanth, A. R.; Abhilash, N.; Biju, Akkattu T. (Accounts of Chemical Research, 2006)
An Account of carbon−carbon and carbon−nitrogen bond-forming reactions mediated by zwitterions generated by the addition of organic nucleophiles to activated unsaturated systems highlighting their synthetic potential is presented.

Employing homoenolates generated by NHC catalysis in carbon-carbon bond-forming reactions: state of the art - Nair, Vijay; Menon, Rajeev S.; Biju, Akkattu T.; Sinu, C. R.; Paul, Rony Rajan; Jose, Anu; Sreekumar, Vellalath (Chemical Society Reviews, 2011)
Homoenolate is a reactive intermediate that possesses an anionic or nucleophilic carbon beta to a carbonyl group or its synthetic equivalent. The recent discovery that homoenolates can be generated from alpha,beta-unsaturated aldehydes via N-Heterocyclic Carbene (NHC) catalysis has led to the development of a number of new reactions. A majority of such reactions include the use of carbon-based electrophiles, such as aldehydes, imines, enones, dienones etc. resulting in the formation of a variety of annulated as well as acyclic products. The easy availability of chiral NHCs has allowed the development of very efficient enantioselective variants of these reactions also. The tolerance showed by NHCs towards magnesium and titanium based Lewis acids has been exploited in the invention of cooperative catalytic processes. This tutorial review focuses on these and other types of homoenolate reactions reported recently, and in the process, updates the previous account published in 2008 in this journal.